Insights Into the Molecular Mechanisms of T Follicular Helper-Mediated Immunity and Pathology - Qin, Lei; Waseem, Tayab C.; Sahoo, Anupama; Bieerkehazhi, Shayahati; Zhou, Hong; Galkina, Elena V.; Nurieva, Roza (Frontiers in Immunology, 2018)
T follicular helper (Tfh) cells have emerged as the key players in providing help to B cells during germinal center reactions. Generating protective antibodies against infections is an important aspect of Tfh cell immunity and the dysregulation of Tfh cell responses has been implicated in a range of disorders such as autoimmunity, inflammation and malignancy. Thus, their differentiation and maintenance must be tightly regulated to ensure appropriate help to B cells. The generation and function of Tfh cells is regulated by multiple checkpoints including their early priming stage in T zones and throughout the effector stage of differentiation in germinal centers. Signaling pathways activated downstream of cytokine and costimulatory receptors as well as consequent activation of subset-specific transcriptional factors are essential steps for Tfh cell generation. Thus, understanding the mechanisms underlying Tfh cell–mediated immunity and pathology will highlight potential targets for novel therapeutic approaches. In this review, we summarize the latest findings related to the regulation of Tfh cell differentiation and their role in normal immune responses and antibody-mediated diseases.